Sleep behaviors and time-to-pregnancy: results from a Guangzhou City cohort - Yuxian Zhang; Dongling Gu; Yanyuan Xie; Bing Li (Reproductive Health)
Abstract Introduction Fertility outcomes are increasingly influenced by modern lifestyle factors, including sleep behaviors. However, the relationship between sleep and time to pregnancy (TTP) is underexplored. Methods We conducted a prospective cohort study of 1,684 couples in Guangzhou, China. Sleep behaviors were assessed via structured interviews. Cox proportional hazards models were used to estimate fecundability ratios (FRs), adjusting for potential confounders. Sleep-wake regularity was assessed for all women. Among those with regular patterns (n = 1506), we further analyzed sleep duration, bedtime, perceived sleep sufficiency, and insomnia. Results Among all participants, 178 (10.6%) had irregular sleep. Time-varying models revealed that compared to regular sleepers, irregular sleepers exhibited a decreasing fecundability ratio (FR < 1) after approximately 2.6 months of attempting pregnancy, with the association becoming statistically significant after 4.1 months. In women with regular sleep, longer sleep duration was associated with higher fecundability (adjusted FR = 1.18, 95% CI: 1.09–1.27; p < 0.001). Spline analysis indicated a linear increase in fecundability with sleep durations exceeding 7.5 h. Perceived insufficient sleep was linked to reduced fecundability (adjusted FR = 0.62, 95% CI: 0.48–0.81; p < 0.001), while later bedtime was associated with lower fecundability (adjusted FR = 0.91, 95% CI: 0.84–0.98; p = 0.045). Insomnia showed no significant effect (adjusted FR = 0.86, 95% CI: 0.67–1.11, p = 0.241). Conclusions Irregular sleep patterns may reduce fecundability over time. Among women with regular sleep, longer duration, earlier bedtime, and sufficient perceived sleep were associated with improved reproductive potential. Sleep optimization could be a modifiable behavioral target to enhance fertility. Trial registration ChiCTR2300068809 registered 1/3/2023.